Perspective: Decolonizing postmodernist approaches to mental health discourse toward promoting epistemic justice - Levin, Lia (Frontiers in Psychiatry, 2022)
Currently, it is possible to observe a slowly (but surely) growing volume of claims seeking to disprove Foucauldian ideas about knowledge and power as overlapping basic theories of epistemic justice. Prompted by these claims, alongside adopting tenets of Critical Race Theory to address injustices inflicted upon people facing mental health challenges, I propose applying decolonizing deconstruction to Foucault’s ‘subject’ and ‘subjugation’ terminology, toward identifying opportunities to enhance epistemic justice, primarily in direct interventions in mental health services.